“Telling My Side of Things”: Tolstoy Novellas into Monologue Drama - Csikai, Zsuzsanna (Hungarian Journal of English and American Studies, 2020)
The paper examines two drama adaptations of Tolstoy’s novellas, Nancy Harris’s The Kreutzer Sonata (2009) and Peter Reid’s Desire (2014), both recent additions to contemporary Irish theatre’s abundant number of adaptations as well as male monologue plays. The exploration of the adaptation strategies assesses how Harris and Reid engage with these nineteenth-century works so that the old narratives are endowed with new relevance. While Harris’s play, which often rises to a poetic quality, innovates with the use of on-stage live music, it remains set in Russia in the past, which makes it a powerful period piece with anachronistic treatment of the central theme of sexual jealousy. In contrast, Reid’s adaptation of Tolstoy’s novella with a similar theme actualizes and relocates the original, transferring it to Ireland in the present time, and through the changes introduced in the plot and character, the playwright creates a credible psychological landscape for twenty-first-century audiences. (ZsCs)